Imaging in Rare Case Parry Romberg Syndrome: Case Report - Wijayanti, Kurnia Arma; Feriastuti, Widiana (Journal of Neonatal Surgery, 2025)
Parry Romberg syndrome (PRS) defined by the gradual and acquired atrophy of one side of the face. There is still a lack of clarity regarding the pathogenesis of PRS. In the etiology of PRS, immune-mediated mechanisms are assumed to be a fundamental role; nevertheless, there is also the possibility that the autonomic nervous system is not functioning correctly. Performing radiological evaluation and subsequent identification of this condition can help mitigate the impact on one's lifestyle and slow down the disease's advancement. In this report, we present an example of this syndrome in 12-year-old boy and intend to provide a detailed description of the many radiological manifestations of this condition.